St. Claire's Church - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the interior of St. Claire's Church. The front altar is bound by two smaller altars with religious statues. A life size figure of Christ on a wooden cross stands to the left of the far right altar.